2019
DOI: 10.1021/acs.est.9b03648
|View full text |Cite
|
Sign up to set email alerts
|

Direct Electron-Transfer-Based Peroxymonosulfate Activation by Iron-Doped Manganese Oxide (δ-MnO2) and the Development of Galvanic Oxidation Processes (GOPs)

Abstract: Manganese oxides have been recently investigated as excellent catalysts for peroxymonosulfate (PMS) activation, and the reported mechanisms are mostly forming reactive oxygen species (ROSs). This study investigated the use of iron-doped manganese oxide, synthesized via air oxidation under strong alkaline conditions. The oxidation of three substrates was affected by their adsorption at the catalyst surface, solution pH, and co-solutes. Common ROS scavengers inhibited the oxidation of bisphenol A (BPA), suggesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
95
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 287 publications
(99 citation statements)
references
References 61 publications
1
95
0
Order By: Relevance
“…BPA decomposition was barely inhibited in the Cu-N 4 /C-B/PMS upon K 2 Cr 2 O 7 addition ( SI Appendix , Fig. S26 B ), suggesting that the system was likely based on direct electron transfer on the catalyst surface other than in solution phase ( 51 ). Moreover, chronoamperometry measurements were performed ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…BPA decomposition was barely inhibited in the Cu-N 4 /C-B/PMS upon K 2 Cr 2 O 7 addition ( SI Appendix , Fig. S26 B ), suggesting that the system was likely based on direct electron transfer on the catalyst surface other than in solution phase ( 51 ). Moreover, chronoamperometry measurements were performed ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The first is the controversy regarding the catalytic mechanisms. Currently, four mechanisms of pollutant degradation and mineralization have been proposed, including sulfate/hydroxyl radicals, singlet oxygen, high-valent metals, and catalyst-mediated electron transfer 12 , 16 18 . However, solid evidence to support these mechanisms is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…45,46 As depicted in the Supporting Information (Figure S16a 47 Although the N-rGO-CoSA/IO 4 − system exhibited slightly lower reaction rates compared to that observed for the N-rGO-CoSA/PMS system, the Co leaching concentration in − consumed (Supporting Information, Figure S17a), indicating that the decomposition of 4-CP and IO 4 − occurred simultaneously; this was very different from the mechanism governing the conventional radical-based oxidation process. 49 The aforementioned result indicated that a nonradical mechanism might dominate the activities of the N-rGO-CoSA/IO 4 − system. Moreover, it was observed that the IO 4…”
mentioning
confidence: 95%